In vitro and in vivo antimicrobial activity of Ulva lactuca Linn. (Green algae) associated endophytic bacterial Strains - Prasanna Habbu, Vijayanand Warad, Rajesh Shastri, Chetan Savant, Smita Madagundi, Prajact Kekare (Journal of Applied Pharmaceutical Science, 2016)
The development of resistance by pathogenic microorganisms to synthetic antibiotics encouraged researchers to find novel drugs for the treatment of infectious diseases. This opened new avenues to investigate the antimicrobial efficacy of active extracts/constituents from plant endophytes. In the present study, we have isolated endophytic bacteria (ULB-I, II and III) from green algae Ulva lactuca Linn. and the same bacteria were used for fermentation and extraction. Chloroform and ethyl acetate fractions of ULB-I, II and III were prepared and screened for in-vitro antimicrobial activities and also against Kleibesella pnumoniae infected mice in-vivo. In-vitro anti-microbial activities of ULB-I, II and III were performed against pathogenic bacteria, fungi and Mycobacterium tuberculosis H37 RV strain. From the phylogenetic analysis, the isolated endophytic organisms were identified as Bacillus subtilis JCM strain (ULB-I) and Enterobacter cloacae NBRC strain (ULB-II and III). ULB–I was found to be active against Staphylococcus aureus (1.6µg/ml) and Enterococcus feacalis (0.2µg/ml). The MIC against Staphylococcus aureus and Kleibesella pnumoniae was found to be 0.4µg/ml for ULB-II. A significant anti-fungal activity was observed against Aspergillus flavus (0.2-3.2µg/ml) and Aspergillus niger (0.2-0.4µg/ml). Further, Chloroform fraction of ULB-II and ethyl acetate fraction of ULB-III have shown significant anti-tubercular activity against the tested organism with MIC of 6.25µg/ml. This was supported by in-vivo antimicrobial activity against K. pneumoniae infection in mice and least hemolytic activity against erythrocytes was observed. HPTLC analysis of above fractions further confirmed the presence of polyvalent secondary metabolites.
Keywords: Endophytic bacteria, Ulva lactuca, antimicrobial, antitubercular, HPTLC.